2019
DOI: 10.1681/asn.2019020183
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Volume and Glomerulosclerosis at Different Depths within the Human Kidney

Abstract: BackgroundAge, CKD risk factors, and kidney function are associated with larger glomerular volume and a higher percentage of globally sclerotic glomeruli. Knowledge of how these associations may differ by cortical depth is limited.MethodsTo investigate glomerular volume and glomerulosclerosis across different depths of cortex, we studied wedge sections of the renal parenchyma from 812 patients who underwent a radical nephrectomy (for a tumor), separately characterizing glomeruli in the superficial (subcapsular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 35 publications
(39 reference statements)
5
57
0
Order By: Relevance
“…The study sample was an expansion of a previously described cohort of patients who are part of the Mayo Clinic Nephrectomy Registry. 10,11 This cohort has undergone a radical nephrectomy for a renal tumor at Mayo Clinic Minnesota from 2000 to 2015. We only studied patients who underwent a complete unilateral nephrectomy for a renal tumor (usually renal cancer) with no metastatic lesions or positive lymph nodes at the time of surgery.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The study sample was an expansion of a previously described cohort of patients who are part of the Mayo Clinic Nephrectomy Registry. 10,11 This cohort has undergone a radical nephrectomy for a renal tumor at Mayo Clinic Minnesota from 2000 to 2015. We only studied patients who underwent a complete unilateral nephrectomy for a renal tumor (usually renal cancer) with no metastatic lesions or positive lymph nodes at the time of surgery.…”
Section: Study Populationmentioning
confidence: 99%
“…Segmental sclerosis was rare and minimal in this cohort. 11 The study was approved by the Mayo Clinic Institutional Review Board.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Puelles et al (2012) found no correlation between glomerular location and volume in human kidneys. However, Denic et al (2019) examined 812 human nephrectomy kidneys and concluded that glomerular volume was highest in the middle cortical region, and lowest superficially, whereas the presence of glomeruli sclerosis was highest in the superficial region.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, while we analyzed 10 whole glomeruli per kidney, we could not determine whether individual glomeruli were located in the inner or outer cortex. This would have been preferable because pathology is often more prevalent in one cortical zone than the other (Denic et al, 2019;Kanzaki et al, 2013;Samuel, Hoy, Douglas-Denton, Hughson, & Bertram, 2005). However, when using the 20x BABB lens to image mouse kidneys it is not possible to be confident about the zonal location of glomeruli.…”
Section: Discussionmentioning
confidence: 99%